Bioinformatics basics : - Buehler, Lukas K. (Taylor & Francis, 2005)
Completely revised and updated, this new edition of a bestseller will continue to serve as a tool that allows researchers to easily access and use databases to gather information on genes, proteins, and diseases. It covers new approaches to data analysis using databases around the world. It identifies computing techniques that help readers manage the massive flow of information. The structure of this second edition will follow that of the first and its content will reflect the growth in information. New sections cover recent developments in genome projects, microarray, proteonics, brain mapping, and more.